RGEC Method Analysis to Measure the Health Level of State-Owned Banks Against Stock Prices in 2011-2022 - Elly, Mohammad Iskak; Krisnawati, Titin (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2023)
Share prices are a reflection of the value of a company. The fundamental conditions of banking companies and central bank policies can influence banking shares. Health assessment is carried out using a risk approach that includes four RGEC components. This research aims to analyze the influence of risk profile, good corporate governance, earnings and capital on share prices of state-owned banks. The type of research used is explanatory research. The research data source is secondary data from state-owned banks that carry out financial reporting on the IDX in 2011-2022. Sampling used purposive sampling with a sample of four state-owned banks. Data analysis uses descriptive analysis, multiple linear regression, and hypothesis testing. The research results show that simultaneously and partially risk profile, good corporate governance, earnings and capital have a significant effect on stock prices. The size of RGEC's contribution to the share price of state-owned banks is 40.2%.